Landmark-based Morphometric analysis on selected species of fishes (Teleostei Leiognathidae - Echem, Roldan T. (2014)
In this investigation, geometric morphometric analysis was used to determine the morphological diversity within and among four species of fishes under Family Leiognathidae and one out-group under Family Menidaea. Two hundred (200) fish samples were collected in the marine waters of Zamboanga City; these included Leiognathus equulus, L. fasciatus, L. bindus, L. Daura and one out-group Mene maculata which showed evolution and diversification of L. fasciatus. Fish samples were scanned at uniform 400 dpi, and the resulting images were binarized using SCIONIMAGE, an image anlysis and processing software. The x and y coordinates of 15 landmark points were collected around the contour of the fish samples. For the landmark analyses, the 15 landmark coefficient were used as variables for multivariate and cluster in order to assess the shape of the fish. Procrustes fitting of the landmark points allowed for the comparison of the various shapes of the fish samples. The resultant shape variables were analyzed to determine differences in form, contour and profile of the fishes using geometric thin- plate spline grinds (TPS), partial warps (PW) and relative warps (RW). The results of this study showed variations in the various species of fishes under Family Leiognathidae and within each species. Significant differences were found among species and these shape changes were related to differences in habitat and feeding habits among the species.
Keywords: Fishes; Marine Biology; Leiognathidae; Mindanao studies